Electrostatic Control of the Thermoelectric Figure of Merit in Ion‐Gated Nanotransistors. (3rd July 2021) - Prete, Domenic; Dimaggio, Elisabetta; Demontis, Valeria; Zannier, Valentina; Rodriguez‐Douton, Maria Jesus; Guazzelli, Lorenzo; Beltram, Fabio; Sorba, Lucia; Pennelli, Giovanni; Rossella, Francesco
Abstract: Semiconductor nanostructures have raised much hope for the implementation of high‐performance thermoelectric generators. Indeed, they are expected to make available reduced thermal conductivity without a heavy trade‐off on electrical conductivity, a key requirement to optimize the thermoelectric figure of merit. Here, a novel nanodevice architecture is presented in which ionic liquids are employed as thermally‐insulating gate dielectrics. These devices allow the field‐effect control of electrical transport in suspended semiconducting nanowires in which thermal conductivity can be simultaneously measured using an all‐electrical setup. The resulting experimental data on electrical and thermal transport properties taken on individual nanodevices can be combined to extract ZT, guide device optimization and dynamical tuning of the thermoelectric properties. Abstract : Suspended nanowire device architectures and ionic liquids enable a new paradigm of an all‐electrical experimental platform for nanoscale energy harvesting. For the first time, all thermoelectric parameters are measured and modulated in the same semiconductor nanostructure. Thermally insulating soft dielectric gates allow maximizing the thermoelectric figure of merit via the field effect.